West Africa during the Atlantic slave trade : archaeological perspectives - DeCorse, Christopher R. (Bloomsbury, 2016)
Surveying archaeological data from West Africa, with sites ranging from the Senegambia to the Cameroon, this volume focuses on data from about 1500, a time period that witnessed dramatic transformations in African political and social life.
Keywords: Excavations (Archaeology) -- Africa, West.; Africa, West -- Antiquities.; Slave trade -- Africa, West.; Fouilles (Archéologie) -- Afrique occidentale.; Traite des esclaves -- Afrique occidentale.; HISTORY -- Africa -- West.; Antiquities; Excavations (Archaeology); Slave trade; West Africa